Mathematical model for degradation and drug release from an intravitreal biodegradable implant - Ferreira, J. A. (2020)
In this paper we study from a mathematical point of view the drug release and the degradation process in the context of biodegradable intravitreal implants. In particular, two different clinical situations are considered: non-vitrectomized and vitrectomized eyes. In the former case we assume that the vitreous humor is replaced by a saline solution or a silicone oil. In intravitreal space, the intravitreal liquid enters the implant by non-Fickian diffusion causing the degradation of the poly(lactic-co-glycolic acid) based implant. Then, drug in the implant dissolves and diffuses out of the polymeric matrix. The transport of drug in the vitreous chamber and retina is modeled by Fickian diffusion and convection generated by the flow of the vitreous humor. In order to numerically solve the system of partial differential equations that define the model, we propose an Implicit–Explicit finite element method that allows for the decoupling of the solution reducing the computational cost of the simulations. Several numerical experiments showing the effectiveness of the proposed numerical schemes are also included. The proposed mathematical model may be useful to optimize patient specific treatments in clinical practice.